Neonatal tetanus treated with diazepam as single antispasmodic agent - Taslim Soetomenggolo; Ratna Heni Purboyo; S. K. Hendarto; Sofyan Ismael (Indonesian Pediatric Society, 1981)
The use of diazepam as single antispasm in treating neonatal tetanus is better than the conventional therapy with the combination of Phenobarbital chlorpromazine and diazepam. The dose of diazepam 10 mg/kg body weight/day can be increased for very severe cases. The overall mortality of this study is 50%. Incubation period of less than 7 day and temperature on admission of more than 39Â°C are important factors to contribute to the high mortality. The critical period of neonatal tetanus is 15 days.